Designing English Listening Materials through YouTube Video Editing: Training for English Teachers of Islamic Junior High Schools, Parepare, South Sulawesi - Zulfah Fakhruddin; Usman Usman; Rahmawati Rahmawati; Sulvinajayanti Sulvinajayanti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study was conducted to help English teachers in designing English listening materials in form of audio and textbook through YouTube video editing. 18 English teachers of 10 Islamic junior high schools in Parepare were trained to write English listening materials in form of textbook and to edit video(download ,import, cut, merge, and export video) in form of audio.150 students were observed and tested to evaluate teachers’ products. Training materials consist of: (1) searching and download video through YouTube, (2) editing video that includes import, cut, merge, and export video, and (3) writing worksheet that contains phoneme discrimination dan listening comprehension exercise in form of multiple choice,true false,and completion. Training activities include: (1) explanation, (2) practice, (3) grouping, (4) assignment/design, and (5) evaluation and revision. After following training, teachers’ ability was categorized into good and fair in designing English listening materials. More than 50% teachers were categorized into good in editing video and 72% teachers were categorized into good in writing listening exercise. Students’ English listening learning outcome was categorized into good after learning by using teachers’ products and students have positive attitude in learning English listening skill.